Densities and dynamic viscosities of ionic liquids having 1-butyl-3-methylimidazolium cation with different anions and bis(trifluoromethylsulfonyl)imide anion with different cations in the temperature range (283.15 to 363.15) K. (January 2018) - Yadav, Anita; Guha, Abhirup; Pandey, Ashish; Pal, Mahi; Trivedi, Shruti; Pandey, Siddharth
Highlights: Densities of ILs of different cations and anions exhibit structural dependence. Density of all ionic liquids vary linearly with temperature. Density depends on the number of F atoms in anion followed by molar mass of ILs. T-dependence of dynamic viscosity follows VFT model and not Arrhenius behavior. Dynamic viscosities of aromatic Im + ILs are lower than those of non-aromatic ILs. Abstract: Ionic liquids have been regarded as promising alternatives to conventional volatile organic solvents. For effective employment of ionic liquids as solvents in various industrial set-ups, the knowledge of their common physical properties is essential. Densities and dynamic viscosities of seven common and popular ionic liquids in the temperature range (283.15 to 363.15) K at 10 K interval are presented. In order to assess the role of the structure of the ionic liquid cation and anion, the selected ionic liquids are comprised of two groups. First group of four ionic liquids is constituted of same 1-butyl-3-methylimidazolium ([bmim + ]) cation and hexafluorophosphate [PF6 − ], ethylsulfate [CH3 CH2 OSO3 − ], trifluoromethysulfonate [CF3 SO3 − ], and bis(trifluoromethylsulfonyl)imide [(CF3 SO2 )2 N − ] anions, and the second group of four ionic liquids is constituted of same [(CF3 SO2 )2 N − ] anion and 1-methyl-1-propylpiperidinium [pmpip + ], N, N, N -trimethylethanolammonium [choline + ], 1-ethyl-3-methylimidazolium [emim + ], and [bmim + ] cations. Decrease in density with increasing temperature is found to follow a simple linear expression for all ionic liquids. Anion of the ionic liquid appears to control the density more than the cation. Density and its temperature dependence depend on the number of fluorine atoms present in the anion of the ionic liquid followed by the molar mass. The temperature dependence of the dynamic viscosity of the ionic liquids is found to be better described by a Vogel–Fulcher–Tamman (VFT) model as opposed to an Arrhenius expression. The two ionic liquids with aromatic imidazolium cations have relatively lower dynamic viscosities as compared to the two with non-aromatic cations.